MEASURING PERCEIVED HAPPINESS OF UNDERGRADUATE STUDENTS IN INSTITUT TEKNOLOGI BANDUNG - Balabagan, Sara Fitria; Pritasari, Adita (Journal of Business and Management, 2018)
Abstract.Happiness is one of the positive emotions that everyone needed, including students. Meanwhile, many students tend to be quite/somewhat happy according to preliminary study research in Institut Teknologi Bandung. This study aims to find the perceived happiness of Students in Institut Teknologi Bandung according to the level of Happiness Index and the factor of studentâ€™s happiness. The sample of this research is Undergraduate Students (N=400) by revering cluster sampling which are Natural Sciences, Engineering, and Social Sciences, Arts, & Humanities. The research instrument was used a closed questionnaire adopted by the Oxford Happiness Questionnaire and happiness factor analysis. The data analysis used quantitative analysis by using descriptive analysis by Excel Program and using Statistical Analysis by using Principal Component Analysis & Ordinal Logistic Regression Method. This research found the Happiness Index Level of the Undergraduate students that most of the Undergraduate students in average are included in Medium Level; The difference of Happiness Index of each cluster; and the happiness factors of Undergraduate Students in overall and each cluster. Therefore, this research generates a recommendation for students, institution and further research to more considering the importance of happiness.Keywords: Happiness, Students Happiness, Happiness FactorÂ Â